Six Saturdays of beyblade and other essays - Jarin, Ferdinand Pisigan (Penguin Random House SEA, 2023)
In these ten personal essays, a father confesses in gripping narratives his coming of age without a father, of working at an early age, of finding love in hopeless places, of losing a son to leukemia, and of accepting the language of pain. In Six Saturdays of Beyblade and Other Essays, bestselling author Ferdinand Pisigan Jarin brings us back to memories of being a tennis ball picker in a lavish country club, of achieving his dreams as the smallest member of a countryside marching band, and of drinking Michael Jordan and Olajuwon as breakfast juice inside a walk-in freezer with fellow service crew members. He also introduces us to his exes and lost first loves. He lends us a list of his fist fights, those he knocked down during drinking sessions or brawls, his antics in the field of love, and the truth behind escaping the convent. Sometimes he is a son, sometimes a father, and sometimes a friend who vividly shares without beating around the bush. Written with a cinematic eye, Jarin bares it all, fair and square, no more or less. Most of all, no entrance fee.-- Back cover.